TRENDS AND CHALLENGES OF AI IMPLEMENTATION IN CRM: SYSTEMATIC LITERATURE REVIEW (SLR) - Andriansyah; Ayel Robbul Barokah; Buhairi; Eko Waluyo; Hairul Rahman (Majapahit Journal of Islamic Finance and Management, 2026)
Customer Relationship Management (CRM) plays a crucial role in strengthening customer loyalty and satisfaction. The integration of Artificial Intelligence (AI) into CRM offers significant benefits such as personalization of customer interactions, prediction of customer needs, and increased operational efficiency. AI enables predictive analysis, automation of repetitive tasks, and 24/7 customer support, all of which contribute to improved service quality and more effective sales strategies. Nonetheless, implementing AI in CRM faces technical, organizational, ethical, and economic challenges, including issues of data privacy, system integration, and user adoption of the technology. This research adopts the Systematic Literature Review (SLR) method to analyze the latest trends, implications, and main challenges in AI-CRM integration. The results show that AI-CRM increases competitiveness and business growth by providing deep insights into customer behavior and preferences. However, successful implementation requires a holistic approach that comprehensively considers strategic, ethical, and economic challenges.